Relationship between Anger Expression in Mothers and Acceptance of Behavior Management Techniques in Pediatric Dentistry - Reihaneh Faghihian; Mehdi Jafarzadeh; Mona Esmaeili; Narges Malek Mohamamdi; Mohammad Hossein Nikbakht (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: The parental acceptance rate of the behavior management methods used in pediatric dentistry is influenced by various factors. Purpose: This study was aimed to investigate the relationship between mothers' anger expression and their acceptance of behavior management methods. Materials and Method: In this cross-sectional study, 110 mothers of children who had less than 12 years of age were recruited. They completed Spielberg's state-trait anger expression inventory (STAXI). The respondents watched an educational video that included explanations of seven behavior management methods. Then, they reported their acceptance of each of these methods using the visual analog scale (VAS). Results: The acceptance rates of behavior management methods from the highest to lowest included tell-show-do, pre-appointment behavior shaping, mouthpiece, voice control, general anesthesia, active restraint, and passive restraint, respectively. There was only a significant inverse relationship between the acceptance of the tell-show-do method and the anger expression (p< 0.05). There was no significant relationship between the acceptance of behavioral management methods and the previous history of a pediatric dental visit, age, and mothers' education. Conclusion: There was a significant inverse relationship between acceptance of the tell-show-do behavioral management method and mothers' anger expression. However, there is no significant relationship between other methods and mothers' anger expression. According to this study, there was a relation between mothers' ages and their acceptance of using a mouthpiece.